Analysis the Use of Artificial Aggregates As a Substitute of Coarse Agreggates for Surface of Flexible Pavement - Mirza Al Mahbubi; Ervina Ahyudanari (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
The quality of flexible pavement construction is strongly influenced by the composition of the material used, including the type of aggregate, and asphalt. Aggregates are generally defined as hard and dense earth shell formation. The mechanical properties of the asphalt mixture are strongly influenced by the fraction and aggregate properties, because the aggregate fills the majority of the asphalt mixture volume (more than 80%) and mass (about 95%). Aggregates have various forms and textures including round and cube shapes. At present, infrastructure development in Indonesia continues to increase the amount of natural aggregate usage, so this will cause the availability of materials to continue to thin out. For this reason, an effort needs to be made to find an alternative to the use of natural aggregate, one of which is the utilization of waste generated by the steam power plant (PLTU), namely fly ash. In this study the artificial aggregate was varied in spherical (AB) form from processed granulaor and angular (ABSC) from processed stone crusher. The results obtained in each variation provide a value that meets the specifications. The full use of artificial aggregates of 25% AB 75% ABSC on dense gradations provides stability of 1258.13 kg. In this study, the use of artificial aggregates can be used as an alternative as an aggregate substitute for nature. In addition to improving mixed quality, the use of artificial aggregates can be an alternative use of waste.